2020
DOI: 10.1088/1367-2630/ab73cd
|View full text |Cite
|
Sign up to set email alerts
|

Learning the dynamics of open quantum systems from their steady states

Abstract: Recent works have shown that generic local Hamiltonians can be efficiently inferred from local measurements performed on their eigenstates or thermal states. Realistic quantum systems are often affected by dissipation and decoherence due to coupling to an external environment. This raises the question whether the steady states of such open quantum systems contain sufficient information allowing for full and efficient reconstruction of the system's dynamics. We find that such a reconstruction is possible for ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…In fact, being the only computational demanding part of the algorithm the calculation of the ground state and and the Bisognano-Wichmann expectation values, in principle one can tackle also higher dimensions by using Monte Carlo techniques. From the quantum engineering viewpoint, another intriguing perspective is to search for Liouvillians that have JG wave functions as unique steady states [94,95]. In particular, dissipation may considerably soften the requirement for longrange couplings thanks to correlations induced by the bath.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…In fact, being the only computational demanding part of the algorithm the calculation of the ground state and and the Bisognano-Wichmann expectation values, in principle one can tackle also higher dimensions by using Monte Carlo techniques. From the quantum engineering viewpoint, another intriguing perspective is to search for Liouvillians that have JG wave functions as unique steady states [94,95]. In particular, dissipation may considerably soften the requirement for longrange couplings thanks to correlations induced by the bath.…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…T . While Lindbladian learning has been recently investigated [11], where it was shown that reconstructing strongly dephasing jump operators is difficult under certain conditions, our focus is on precisely estimating the Hamiltonian component, possibly at the expense of the environmental sector.…”
Section: Open System Generalizationmentioning
confidence: 99%
“…Recent progress has been made in reconstructing generic local Hamiltonians from measurements on single eigenstates and steady states of closed and open systems [18][19][20][21][22][23][24] as well as in the development of more specialized approaches tailored to concrete models [25][26][27][28][29][30][31][32]. An area of research that poses specific challenges for numerical methods and thus Hamiltonian tomography is out-of-equilibrium physics [33][34][35].…”
Section: Introductionmentioning
confidence: 99%